Advancing digital agriculture for climate resilience and economic transformation in Malawi - Matchaya, Greenwell C.; Ebrahim, Girma Yimer; Aheeyar, Mohamed M. M.; Ajayi, O. C.; Ajilore, O. (International Water Management Institute, 2025)
Malawi, a landlocked country in Southeastern Africa, is vulnerable to the impacts of  climate change. Agriculture is the backbone of its economy, supporting more than 80%  of the population, contributing 30% to the national Gross Domestic Product (GDP),  and generating 80% of export earnings. The World Bank projects that,  under a business-as-usual scenario, climate change could reduce Malawi’s GDP by 3–9% by 2030, 6–20% by 2040 and 8–16% by 2050. These losses are primarily attributed to infrastructure damages, including roads and bridges, and decreased labor productivity due to heat stress. Additionally, climate shocks could push an estimated two million people into poverty by 2030 and increase to four million by 2040. However, this critical sector is largely dominated  by smallholder farmers who rely on rainfed systems and face persistent structural,  technological, and climate-related challenges. As climate variability intensifies—bringing  more frequent droughts, floods, and erratic rainfall—the urgency to adapt and innovate  to ensure the resilience of the country’s agrifood system becomes paramount. In this context, digital agriculture offers a transformative pathway to improve productivity,  resilience, and inclusivity in the face of climate and economic uncertainty. This brief synthesizes findings from a study conducted by the International Water Management Institute (IWMI) and the Global Center on Adaptation (GCA). Drawing on literature reviews, field consultations, and surveys from districts including Lilongwe, Dowa, Zomba and Mchinji, the report evaluates the role of digital agriculture in climate adaptation, identifies barriers to adoption, and proposes strategic investments for inclusive agricultural transformation.